2002
DOI: 10.1021/jo0261698
|View full text |Cite
|
Sign up to set email alerts
|

Mild Method for Cleavage of Dehydroalanine Units:  Highly Efficient Conversion of Nocathiacin I to Nocathiacin IV

Abstract: Thiazolyl peptide antibacterial nocathiacin I (1) was converted to nocathiacin IV (4) in high yield using iodomethane and hydriodic acid in THF at 45 degrees C. Several simplified dehydroalanine-containing systems undergo dehydroalanine cleavage under the same conditions, although in these cases iodomethane is not needed for efficient conversion. The mild reaction conditions are in contrast with other methods described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
2
14
0
2
Order By: Relevance
“…[16] We found that cropping of the dehydroamino acid tail [17,18] of 1 was crucial to allow clean transformations. With Et 2 NH in CHCl 3 the compounds 4 or 5 could be obtained on preparative scale after simple flash chromatography (Scheme 1).…”
mentioning
confidence: 99%
“…[16] We found that cropping of the dehydroamino acid tail [17,18] of 1 was crucial to allow clean transformations. With Et 2 NH in CHCl 3 the compounds 4 or 5 could be obtained on preparative scale after simple flash chromatography (Scheme 1).…”
mentioning
confidence: 99%
“…Solvent was pumped from the top using a FMI pump. The column was eluted with two column volumes each of 1:4 hexane-DCM (fraction 3) and 2.5% MeOH-DCM (fractions 4-6), 1.5 column volume of 5% MeOH-DCM(fractions7-11),onecolumnvolumeof10%MeOH-DCM (fractions [12][13][14][15], and 1.5 column volumes each of 20% (fraction [16][17][18], 50% (19)(20)(21), and finally 100% MeOH. Fractions were pooled based on TLC analysis and analytical HPLC, affording fractions 1-24 as listed in parentheses with the elution solvents.…”
Section: Methodsmentioning
confidence: 99%
“…This was exemplified by chemical modifications of nocathiacin I, including a recent method developed for efficient hydrolysis of the side chain. [14][15][16][17][18][19][20][21][22][23] These successes bolstered our thought process, and we initiated an investigation to discover new thiazolyl peptides with chemical functionalities that can provide additional opportunities for chemical modifications, which could lead to compounds with better physical and pharmaceutical properties. Such compounds could be amenable to development as new antibiotics without cross resistance to existing antibiotics.…”
mentioning
confidence: 99%
“…[35] Der Abbau des Schwanzteils ist ebenfalls vielfach durchgeführt worden und gestattet je nach den gewählten Reaktionsbedingungen den Zugang zu zwei verschiedenen Produkten: dem Thiazol-4-carbonsäure-Derivat (Nocathiacinsäure) oder dem entsprechenden Amid (Nocathiacin IV). [36,37] Nocathiacinsäure muss nicht zur Steigerung der Lçslichkeit modifiziert werden, oder sie kann nachfolgend mit Aminen kondensiert werden. [38,39] Nocathiacin IV ist in einer Ein-Topf-Sequenz aus N-Alkylierung und reduktiver Aminierung umgesetzt worden, um lange Alkylschwänze in das Molekül einzuführen, ähnlich wie in 13 (Abbildung 5 c).…”
Section: Einführungunclassified